If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -1 = 5 + -2x Reorder the terms: -1 + -3x = 5 + -2x Solving -1 + -3x = 5 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -1 + -3x + 2x = 5 + -2x + 2x Combine like terms: -3x + 2x = -1x -1 + -1x = 5 + -2x + 2x Combine like terms: -2x + 2x = 0 -1 + -1x = 5 + 0 -1 + -1x = 5 Add '1' to each side of the equation. -1 + 1 + -1x = 5 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 5 + 1 -1x = 5 + 1 Combine like terms: 5 + 1 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| (5n+2)(2n-3)= | | 16x^4+6x^2= | | (3x-4)(x-2x^2-6)= | | (3-2y)(8-y)= | | (y-9)(y+9)= | | (m+1)(m+1)= | | (a-5)(a+3)= | | 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x | | x/6=12/8 | | 20/16=70/x | | 6/12=n/42 | | -4/5*(4a-1)=28 |